Monatomic cobalt-based composite catalyst, preparation method thereof and application of monatomic cobalt-based composite catalyst in degrading antibiotics by activating peroxymonosulfate

By preparing a single-atom cobalt-based catalyst supported on biochar, the problem of low PMS activation efficiency was solved, and the efficient degradation of organic pollutants in antibiotic wastewater was achieved, exhibiting good stability and reusability.

CN121402085APending Publication Date: 2026-01-27XINXIANG MEDICAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511591770.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-03
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

Existing transition metal activated peroxymonosulfate (PMS) technology suffers from low activation efficiency, high cost, and difficulty in large-scale application when degrading antibiotic wastewater.

Method used

A single-atom cobalt-based composite catalyst was prepared by mixing biomass powder with cobalt nitrate hexahydrate, centrifuging, drying, and pyrolysis to produce a single-atom cobalt-based catalyst supported on biochar. The catalyst's high specific surface area and abundant pore structure were utilized to promote PMS activation and improve antibiotic degradation efficiency.

Benefits of technology

Under dark conditions, the single-atom cobalt-based composite catalyst can efficiently activate PMS, with a tetracycline removal rate of over 99%. It exhibits good stability and reusability, and is suitable for the degradation of common organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121402085A_ABST
    Figure CN121402085A_ABST
Patent Text Reader

Abstract

The invention provides a monatomic cobalt-based composite catalyst, a preparation method of the monatomic cobalt-based composite catalyst and application of the monatomic cobalt-based composite catalyst to degradation of antibiotics by activating peroxymonosulfate, and belongs to the technical field of advanced oxidation. The method comprises the following steps: mixing biomass powder and water to obtain a biochar suspension, adding cobalt nitrate hexahydrate into the biochar suspension, centrifuging the mixed solution, collecting residues, and drying to obtain a sample; and pyrolyzing the sample in a protective gas atmosphere, taking out, cooling, washing, and drying to obtain the monatomic cobalt-based composite catalyst. The cobalt-based catalyst prepared by the invention has high specific surface area, abundant pore structures and a large number of active sites, and is beneficial to activation of PMS and degradation of pollutants; the cobalt-based composite catalyst prepared by the method is used for activating peroxymonosulfate to degrade tetracycline, and the removal rate of tetracycline in a solution is greater than 99% after reaction is carried out for 20 minutes under a dark condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of advanced oxidation technology, and in particular to a single-atom cobalt-based composite catalyst, its preparation method, and its application in the degradation of antibiotics by activated peroxymonosulfate. Background Technology

[0002] Currently, activated persulfate (PMS-AOP) advanced oxidation technology is considered one of the key technologies for treating antibiotic wastewater due to its powerful oxidation capacity and high degradation efficiency. AOP, as a novel wastewater treatment technology, features environmental friendliness, low energy consumption, simple operation, strong oxidation capacity, high mineralization rate, and wide application range. In this technology, persulfate (PMS) can be activated through various methods such as ultraviolet radiation, heating, or transition metals to generate highly reactive substances such as sulfate radicals and hydroxyl radicals, thereby mineralizing organic pollutants into inorganic small molecules such as CO2 and H2O. Among these, transition metal activation, due to its free external energy input and simple operation, is considered a highly efficient and promising PMS activation method.

[0003] Single-atom catalysts (SACs), as a novel type of catalyst with single-atom dispersed metal active centers, have received special attention in the field of catalysis in recent years due to their ease of recovery as heterogeneous catalysts and their high activity and selectivity as homogeneous catalysts. Summary of the Invention

[0004] The purpose of this invention is to provide a single-atom cobalt-based composite catalyst, its preparation method, and its application in the degradation of antibiotics by activated peroxymonosulfate, in order to solve the above-mentioned technical problems.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a single-atom cobalt-based composite catalyst, comprising the following steps: 1) Biochar suspension was obtained by mixing biomass powder and water. Cobalt nitrate hexahydrate was added to the biochar suspension. The mixture was centrifuged, the residue was collected and dried to obtain the sample. 2) The sample was pyrolyzed under a protective gas atmosphere, and after cooling, it was washed and dried to obtain a single-atom cobalt-based composite catalyst.

[0006] Furthermore, the mass ratio of the biomass powder to cobalt nitrate hexahydrate is 0.8~1.2:1.5~4.2, and the mass fraction of cobalt in the mixed solution is 10~18%. The biomass powder includes one or more of corn straw powder, wheat straw powder, and rice straw powder.

[0007] Furthermore, in step 1), the mixing is carried out under stirring, with a stirring speed of 500~800 rpm and a stirring time of 1~2 hours.

[0008] Furthermore, the centrifugation speed is 3500~6000 r / min, and the centrifugation time is 5~10 min.

[0009] Furthermore, the pyrolysis temperature is 500~700℃, and the pyrolysis time is 2~5h.

[0010] Furthermore, the protective gas includes nitrogen, argon, or helium; the washing solvents are water, anhydrous ethanol, and hydrochloric acid, respectively.

[0011] The present invention also provides a single-atom cobalt-based composite catalyst prepared by the above preparation method.

[0012] This invention also provides the application of a single-atom cobalt-based composite catalyst in the activation of peroxymonosulfate degradation of antibiotics.

[0013] The beneficial effects of this invention are: (1) The tubular porous structure of biochar has a high specific surface area, which can provide a large number of sites for metal loading and reduce the aggregation of active sites; the nitrogen lone pair can act as an electron donor to form metal-nitrogen (MN) bonds with metal ions, promote electron transfer and redox processes, thereby improving the activation efficiency of PMS; the single-atom cobalt-based composite catalyst (Co@Biochar) prepared in this invention has low raw material cost, simple preparation process and is easy to mass-produce, and has strong practicality.

[0014] (2) The single-atom cobalt-based composite catalyst prepared in this invention has Co single atoms loaded on biochar, which makes the catalyst have a high specific surface area, rich pore structure and a large number of active sites, which helps to activate PMS and degrade pollutants. When the cobalt-based composite catalyst prepared in this invention is applied to activate peroxymonosulfate to degrade tetracycline, the removal rate of tetracycline in the solution is greater than 99% after reacting for 20 min under dark conditions.

[0015] (3) The cobalt-based catalyst prepared by the present invention has good charge migration efficiency, excellent PMS activation efficiency under dark conditions, high pollutant degradation ability, good stability and reusability, and can be widely used in the degradation of common organic pollutants. Attached Figure Description

[0016] Figure 1 The image shows the field emission scanning electron microscope characterization of the cobalt-based catalyst in Example 1. Figure 2 This is a transmission electron microscope (TEM) characterization image of the cobalt-based catalyst in Example 1; Figure 3 The following is a nitrogen adsorption-desorption isotherm diagram of biochar and cobalt-based catalyst in Example 1 (Relative pressure is relative pressure, Quantity adsorption is the amount of adsorption). Figure 4 The diagram shows the pore size distribution of the biochar and cobalt-based catalyst in Example 1 (Pore diameter is the pore size, and Pore volume is the pore volume). Figure 5 This is a high-angle annular dark-field scanning transmission electron microscope image of the single-atom cobalt-based composite catalyst in Example 1; Figure 6 This is a diagram showing the effect of the single-atom cobalt-based catalyst activating peroxymonosulfate to degrade tetracycline in Example 2. Detailed Implementation

[0017] This invention provides a method for preparing a single-atom cobalt-based composite catalyst, comprising the following steps: 1) Biochar suspension was obtained by mixing biomass powder and water. Cobalt nitrate hexahydrate was added to the biochar suspension. The mixture was centrifuged, the residue was collected and dried to obtain the sample. 2) The sample was pyrolyzed under a protective gas atmosphere, and after cooling, it was washed and dried to obtain a single-atom cobalt-based composite catalyst.

[0018] In this invention, the mass ratio of biomass powder to cobalt nitrate hexahydrate is 0.8~1.2:1.5~4.2, preferably 0.9~1.1:1.5~3.0, more preferably 0.95~1.05:2.5~3.0, and the mass fraction of cobalt in the mixed solution is 10~18%, preferably 10~17%, more preferably 14~16%.

[0019] In this invention, the biomass powder is preferably one or more of corn straw powder, wheat straw powder, and rice straw powder, with corn straw powder being the most preferred.

[0020] In this invention, in step 1), the mixing is carried out under stirring, the stirring speed is 500~800 rpm, preferably 600~700 rpm; the stirring time is 1~2 hours, preferably 1.5 hours.

[0021] In this invention, the drying temperature is 50~70℃, preferably 55~65℃, more preferably 58~62℃, and the drying time is 10~13h, preferably 11~13h, more preferably 11.5~12.5h.

[0022] In this invention, the centrifugation speed is 3500~6000 r / min, preferably 4000~5500 r / min, and more preferably 4500~5000 r / min; the centrifugation time is 5~10 min, preferably 6~9 min, and more preferably 7~8 min.

[0023] In this invention, the pyrolysis temperature is 500~700℃, preferably 550~650℃, more preferably 580~620℃, and even more preferably 600℃; the pyrolysis time is 2~5h, preferably 2.5~4h, and even more preferably 2.5~3.5h.

[0024] In this invention, the mass fraction of cobalt in the single-atom cobalt-based composite catalyst is preferably 10-13%, more preferably 15-18%, and even more preferably 14-16%.

[0025] In this invention, the protective gas includes nitrogen, argon or helium, preferably nitrogen.

[0026] In this invention, the washing is performed sequentially as a first wash, a second wash, and a third wash; the reagent for the first wash is deionized water, the reagent for the second wash is anhydrous ethanol, and the reagent for the third wash is hydrochloric acid; the first wash is preferably performed at least twice, more preferably at least three times, and even more preferably at least four times; the second wash is preferably performed at least once, more preferably at least twice, and even more preferably at least three times; and the third wash is preferably performed at least once, more preferably at least twice, and even more preferably at least three times.

[0027] The present invention also provides a single-atom cobalt-based composite catalyst prepared by the above preparation method.

[0028] This invention also provides the application of a single-atom cobalt-based composite catalyst in the activation of peroxymonosulfate degradation of antibiotics.

[0029] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0030] Example 1

[0031] 1.2 g of corn straw powder and 1.64 g of cobalt nitrate hexahydrate were added to 50 mL of deionized water, and magnetically stirred at 850 rpm for 1.5 h. The mixed solution was centrifuged at 3500 rpm for 10 min, dried at 60 °C for 12 h, and then the dried sample was ground into powder and transferred to a muffle furnace. Under a nitrogen atmosphere, pyrolysis treatment was carried out at 550 °C for 3 h to obtain a biochar-supported single-atom cobalt-based composite catalyst. After that, it was washed twice with deionized water, twice with absolute ethanol, and twice with 1 M hydrochloric acid. The biochar-supported single-atom cobalt-based composite catalyst was obtained.

[0032] The biochar-supported single-atom cobalt-based composite catalyst prepared in this example was characterized by field emission electron scanning microscopy and transmission electron microscopy respectively, and the field emission electron scanning microscopy characterization diagram of the biochar-supported single-atom cobalt-based composite catalyst was obtained, as Figure 1 shown; the transmission electron microscopy characterization diagram of the biochar-supported single-atom cobalt-based composite catalyst, as Figure 2 shown. It can be observed from Figure 1 that the synthesized biochar-supported single-atom cobalt-based composite catalyst has a tubular, porous structure, and uniformly sized spherical particles can be clearly observed on the surface of the biochar. The formation of this structure is due to pyrolysis under anaerobic conditions. In Figure 2 the lattice fringes of the graphitized structure can be observed.

[0033] The biochar-supported single-atom cobalt-based composite catalyst prepared in this example was subjected to nitrogen adsorption-desorption test, and the nitrogen adsorption-desorption isotherm diagram of the biochar-supported single-atom cobalt-based composite catalyst was obtained, as Figure 3 shown. It can be observed from the figure that all the isotherms are type IV curves with an H3 hysteresis loop, and show strong adsorption at 0.9 < P / P0 < 1, indicating the presence of a mesoporous structure. In addition, compared with the biochar, the specific surface area of the biochar-supported single-atom cobalt-based composite catalyst increased significantly to 124.71 m 2 ·g -1 , and the large specific surface area also endows the composite catalyst with more surface active sites.

[0034] The biochar and the biochar-supported single-atom cobalt-based composite catalyst prepared in this example were subjected to pore size distribution test, and the pore size distribution diagrams of the biochar and the biochar-supported single-atom cobalt-based composite catalyst were obtained, as Figure 4 shown. It can be observed from the figure that the total pore volume of the biochar-supported single-atom cobalt-based composite catalyst sample is larger than that of the biochar. Generally speaking, the biochar-supported single-atom cobalt-based composite catalyst has a large surface area and a rich pore structure, which will provide more surface reaction sites, be conducive to the adsorption and degradation of PMS and pollutants, and thus improve the catalytic performance.

[0035] The biochar-supported cobalt-based composite catalyst prepared in this embodiment was characterized by aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). The high-angle annular dark-field STEM image of the biochar-supported cobalt-based composite catalyst is shown below. Figure 5 As shown in the figure, the presence of single-atom cobalt on the biochar surface can be observed. This demonstrates that the presence of cobalt in single-atom form is beneficial for PMS activation and pollutant degradation, thereby improving catalytic performance.

[0036] Example 2

[0037] 1.0 g of corn stalk powder and 2.96 g of cobalt nitrate hexahydrate were added to 50 mL of deionized water and magnetically stirred at 900 rpm for 2 h. The mixture was then centrifuged at 3600 rpm for 5 min and dried at 60 °C for 12 h. The dried sample was then ground into powder and transferred to a muffle furnace for pyrolysis at 500 °C for 3 h under a nitrogen atmosphere to obtain a biochar-supported single-atom cobalt-based composite catalyst. After the pyrolysis, the catalyst was washed three times with deionized water, twice with anhydrous ethanol, and twice with 1 M hydrochloric acid. The biochar-supported single-atom cobalt-based composite catalyst was thus obtained.

[0038] Take 50 mL of a 20 mg / L tetracycline solution, add the biochar-supported cobalt-based composite catalyst prepared in this example, stir for 60 min in the dark, take a sample for filtration and analysis, then add 1 mmol of PMS solution. After the addition is complete, start timing, take samples for filtration and analysis at time points of 2 min, 4 min, 6 min, 8 min, 10 min, 12 min, 14 min, 16 min, and 18 min, respectively. The effect of the biochar-supported cobalt-based composite catalyst on the activation of peroxymonosulfate for tetracycline degradation in this embodiment is shown in the graph. Figure 6 As shown in the figure, after reacting for 18 minutes in the dark, the removal rate of tetracycline in the solution was greater than 99%.

[0039] Example 3

[0040] 1.0 g of corn stalk powder and 4.036 g of cobalt nitrate hexahydrate were added to 50 mL of deionized water and magnetically stirred at 900 rpm for 2 h. The mixed solution was centrifuged at 3600 rpm for 5 min and dried at 60 °C for 12 h. The dried sample was then ground into powder and transferred to a muffle furnace for pyrolysis at 500 °C for 3 h under a nitrogen atmosphere to obtain a biochar-supported single-atom cobalt-based composite catalyst. After the pyrolysis, the catalyst was washed three times with deionized water, twice with anhydrous ethanol, and twice with 1 M hydrochloric acid. The biochar-supported single-atom cobalt-based composite catalyst was obtained. The activation performance of the cobalt-based composite catalyst obtained in this example was tested using the same test method as in Example 2. The results showed that after reacting for 30 min in the dark, the removal rate of tetracycline in the solution was greater than 99%.

[0041] As can be seen from the above embodiments, the present invention provides a single-atom cobalt-based composite catalyst, its preparation method, and its application in the degradation of antibiotics by activated peroxymonosulfate. The single-atom Co is loaded on biochar, which gives the catalyst a high specific surface area, abundant pore structure, and a large number of active sites, which helps to activate PMS and degrade pollutants. When the single-atom cobalt-based composite catalyst prepared by the present invention is applied to the degradation of tetracycline by activated peroxymonosulfate, the removal rate of tetracycline in the solution is greater than 99% after reacting for 60 min under dark conditions.

[0042] Comparative Example 1

[0043] Same as Example 1, except that copper nitrate hexahydrate is used instead of cobalt nitrate hexahydrate.

[0044] Using the same test method as in Example 2, it was found that the removal rate of tetracycline in the solution of the catalyst obtained in this comparative example was only 85% after reacting in the dark for 30 minutes.

[0045] Comparative Example 2

[0046] Same as Example 1, except that the pyrolysis temperature is 800℃.

[0047] Using the same test method as in Example 2, it was found that the removal rate of tetracycline in the solution after the catalyst obtained in this comparative example reacted for 30 minutes in the dark was only 87%.

[0048] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a single-atom cobalt-based composite catalyst, characterized in that, Includes the following steps: 1) Biochar suspension was obtained by mixing biomass powder and water. Cobalt nitrate hexahydrate was added to the biochar suspension. The mixture was centrifuged, the residue was collected and dried to obtain the sample. 2) The sample was pyrolyzed under a protective gas atmosphere, and after being taken out, cooled, washed, and dried, a single-atom cobalt-based composite catalyst was obtained.

2. The method for preparing the single-atom cobalt-based composite catalyst according to claim 1, characterized in that, The mass ratio of biomass powder to cobalt nitrate hexahydrate is 0.8~1.2:1.5~4.2, and the mass fraction of cobalt in the mixed solution is 10~18%. The biomass powder includes one or more of corn straw powder, wheat straw powder, and rice straw powder.

3. The method for preparing the single-atom cobalt-based composite catalyst according to claim 1 or 2, characterized in that, In step 1), the mixing is carried out under stirring at a speed of 500-800 rpm for 1-2 hours.

4. The method for preparing the single-atom cobalt-based composite catalyst according to claim 3, characterized in that, The centrifugation speed is 3500~6000 r / min, and the centrifugation time is 5~10 min.

5. The method for preparing a single-atom cobalt-based composite catalyst according to claim 1, 2, or 4, characterized in that, The pyrolysis temperature is 500~700℃, and the pyrolysis time is 2~5h.

6. The method for preparing the single-atom cobalt-based composite catalyst according to claim 1, characterized in that, The protective gas includes nitrogen, argon, or helium; the washing solvents are water, anhydrous ethanol, and hydrochloric acid, respectively.

7. The single-atom cobalt-based composite catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. The application of the single-atom cobalt-based composite catalyst according to claim 7 in the activation of peroxymonosulfate degradation of antibiotics.

Citation Information

Cited By

  • Manganese-cobalt bimetal modified bismuth vanadate catalytic material as well as preparation method and application thereof

    CN122124810A